How Do High School Students Perceive Magnets (Mental Models about Magnets, Magnetic Fields, and Magnetic Force)? - Ninik Rikha; Farhadi Farhadi; Anisak Intan; Rikardus F Nikat; M Lukman (Berkala Ilmiah Pendidikan Fisika, 2026)
This study aims to explore the initial knowledge of high school students about magnets from two schools with different PUSPRESNAS science and technology scores, namely SMA Islam NU Pujon with a score of 0 and MAN Kota Batu with a score of 50. The research sample was selected randomly from grades X and XI, with the assumption that the research sample had gained knowledge about the concept of magnets at the previous level. The research method was qualitative descriptive. Data collection was carried out through clinical interviews. The results of the interviews were analyzed and represented in the form of categorization. The findings of the interview results showed that all research samples had the same mental model about magnets, namely: 1. Magnets interact with iron, copper, and aluminum and do not interact with wood, paper, and other non-conductive materials. 2. Magnets have separate north and south poles. 3. Magnetic fields and magnetic forces depend on distance: If the magnet is closer to the object, the magnetic field and magnetic force will be stronger and vice versa. 4. Magnetic properties are only collected at the poles. 5. The strength of a magnet is determined by its size. 6. Magnetic fields are only created by magnets. 7. Field lines are only formed outside the magnet.